2016
DOI: 10.1038/srep22049
|View full text |Cite
|
Sign up to set email alerts
|

Hiding true emotions: micro-expressions in eyes retrospectively concealed by mouth movements

Abstract: When we encounter someone we dislike, we may momentarily display a reflexive disgust expression, only to follow-up with a forced smile and greeting. Our daily lives are replete with a mixture of true and fake expressions. Nevertheless, are these fake expressions really effective at hiding our true emotions? Here we show that brief emotional changes in the eyes (micro-expressions, thought to reflect true emotions) can be successfully concealed by follow-up mouth movements (e.g. a smile). In the same manner as b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 54 publications
1
32
0
Order By: Relevance
“…The more spontaneous movement in the upper face may lead to the more accurate mimicking by the upper face when the duration of expression is very short, since the more spontaneous mimicking in upper face may be less dependent on attention and memory ( Ross et al, 2007 ). Consistently, previous studies found that the lower face had more perceptual weight in the perception of micro-expressions ( Iwasaki and Noguchi, 2016 ) and the Chinese participants paid more attention to the lower part of face while interpreting facial expressions ( Mu et al, 2017 ). In addition, the more voluntary movement in the lower face means that it relies more on attention and consciousness.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The more spontaneous movement in the upper face may lead to the more accurate mimicking by the upper face when the duration of expression is very short, since the more spontaneous mimicking in upper face may be less dependent on attention and memory ( Ross et al, 2007 ). Consistently, previous studies found that the lower face had more perceptual weight in the perception of micro-expressions ( Iwasaki and Noguchi, 2016 ) and the Chinese participants paid more attention to the lower part of face while interpreting facial expressions ( Mu et al, 2017 ). In addition, the more voluntary movement in the lower face means that it relies more on attention and consciousness.…”
Section: Discussionsupporting
confidence: 86%
“…The recent evidence showed that facial feedback signals from the full face are disruptive cues for the recognition of subtle micro-expressions ( Wu et al, 2016 ). Growing evidence also found that the lower face has more weight in facial expression recognition (e.g., Calvo et al, 2013a ; Iwasaki and Noguchi, 2016 ), which suggest that the lower face is the main source of disruption for the recognition of subtle micro-expressions. Therefore, we predicted that amplifying facial feedback of the lower face can reduce the recognition accuracy for subtle micro-expressions.…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have analyzed the movements of skin and soft tissue in the mouth and eye regions to assess the differences between genuine and fake smiles (Calvo et al 2013;Iwasaki and Noguchi, 2016;Jaffer et al, 2016). While both genuine and fake smiles share a contraction of the zygomaticus major (Zmj) muscle that pulls up the corners of the mouth, only a genuine smile also recruits the orbicularis oculi (OOc) muscle around the eyes (Russell and Fernández-Dols, 1997;Duchenne and Cuthbertson, 2006;Iwasaki and Noguchi, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Similar optimum parameter setup can be observed in [29] for action recognition problem. Also, [11] shows that 150 ms frame interval is reasonable to assess micro-level emotional changes for real-fake expression prediction.…”
Section: Implementation Detailsmentioning
confidence: 95%